Driving Engagement on Instagram: A Comparative Analysis of Amazon Prime and Disney+ - Kazi Turin Rahman (SEISENSE Business Review)
Purpose- This paper dives into the engagement patterns exhibited on Instagram by two streaming heavyweights; Amazon Prime and Disney+. With ever-growing popularity among the younger generation, Instagram is vital for driving engagement in the social media ecosystem. Hence, it is crucial to understand what content posted by streaming services fosters engagement on this platform.